The survivor [large type] - Johansen, Iris (Johansen, Iris. Eve Duncan forensics thriller, 2023)
Traveling to Palanan Island in Southeast Asia, archaeologist Riley Smith is aware of the threat from treasure hunters who have no qualms about killing to get what they want. When she successfully evades them and finds the perfectly preserved body of a female warrior, it is just what she needs to entice Eve Duncan to join her. As they seek answers to the questions the body has raised, their discovery will change history-- if they can escape the island and survive long enough to share it with the world. -- adapted from jacket